Evaluation Of Traffic Performance Due To The Establishment Of The New Shopping Center: (Case Study Sunrise Mall Benteng Pancasila Street Mojokerto) - Mochammad Dwiki; Diah Ayu Restuti (Journal of World Conference (JWC), 2020)
The more rapid development of a region will also be followed by the increasing volume of traffic that occurs. With the operation of Sunrise Mall in the city of Mojokerto will bring a change in the increase in traffic volume. The purpose of this study was to determine the magnitude of the generation that occurred due to the opening of Sunrise Mall in the city of Mojokerto. Knowing the traffic performance around Sunrise Mall in the city of Mojokerto in the existing condition which only reviews Degrees of Saturation. Knowing the impact of traffic caused by the operation of Sunrise Mall in the city of Mojokerto. Know the alternatives that can be used to improve intersection, braid and road performance around Sunrise Mall in Mojokerto city and to find out the parking capacity and Parking Space Unit needed at Sunrise Mall in Mojokerto city. Secondary data collection in research includes geometric data on roads, data on traffic volume and intersections, data in and out of the Sunrise Mall building, data on Sunrise Mall characteristics and building area. Results showed that there was an influence of the construction of a new shopping center on traffic performance in the case study of Sunrise Mall Benteng Pancasila Mojokerto Street.